Evaluation of Hypothermia in Sick Neonates as Predictor of Fatality at a Tertiary Care Center of Eastern Nepal - Kanodia, Piush; Bhandari, R; Bhatta, N; Yadav, S (Journal of Nepalgunj Medical College, 2018)
Introduction: Hypothermia is a common and frequent problem in newborns. It has larger impact in outcome related to management of sick infants. Objective: To correlate the severity of hypothermia in sick extramural neonates with fatality and physiological derangements. Materials and Methods: This prospective observational study was carried out at Neonatology unit of Pediatric department of B. P. Koirala Institute of Health Sciences (BPKIHS) Dharan. Total 200 extramural hypothermic neonates were transferred to BPKIHS from June 2015 to June 2016. Neonates weighing more than 1000 g, with abdominal skin temperature less than 36.5°C at admission were included in the study.. Clinical features and associated features were recorded at the time of admission. Oxygen saturation was recorded by a pulse oximeter. Results: Fatality was observed to be 39.3% in mildly hypothermic babies, 51.6% in moderately hypothermic babies and 80% in severely hypothermic babies. However, the presence of associated illness (birth asphyxia, neonatal sepsis and respiratory distress), physiological derangements (hypoxia, hypoglycemia and shock) and weight less than 2000 g were associated with more than 50% fatality even in mildly hypothermic babies. When moderate hypothermia was associated with hypoxia or shock, the fatality was 83.3% and 90.9%, respectively. Similarly, mild hypothermia with hypoglycemia was associated with 71.4% fatality. Conclusion: The presence of associated illness (birth asphyxia, neonatal sepsis and respiratory distress), physiological derangements (hypoxia, hypoglycemia and shock) and weight less than 2000 g should be considered adverse factors in hypothermic neonates. Their presence should classify hypothermia in the next higher category of severity in WHO classification. JNGMC Vol. 14 No. 2 December 2016, page: 8-11